Discussion on the Structure Stability and the Luminescence Switch under Irradiation of a Ce‐Doped Elpasolite Compound. Issue 13 (9th February 2015) - Cornu, Lucile; Gaudon, Manuel; Veber, Philippe; Villesuzanne, Antoine; Pechev, Stanilas; Garcia, Alain; Jubera, Véronique
Abstract Ce‐doped Rb2KInF6 elpasolite has the potential for tunable luminescence due to an unusual reversible redox process between the cerium and indium cations. Coupled with a deep understanding of the luminescence properties, XRD analysis and DFT calculations are used to locate the doping elements in the host lattice. The origin explanation of the charge‐transfer mechanism that causes a decrease or increase in the blue–green cerium emission in opposition to the red indium emission is discussed regarding the crystallographic structure, the connection of the metallic cations and their equilibrium valence. Still detectable after nineteen years, the optical contrast created under irradiation makes this material a good candidate as photosensor for data storage.